Reduced complexity of force and muscle activity during low level isometric contractions of the ankle in diabetic individuals. (February 2017) - Suda, E.Y.; Madeleine, P.; Hirata, R.P.; Samani, A.; Kawamura, T.T.; Sacco, I.C.N.
Abstract: Background: This study evaluated the structure and amount of variability of surface electromyography (sEMG) patterns and ankle force data during low-level isometric contractions in diabetic subjects with different degrees of neuropathy. Methods: We assessed 10 control subjects and 38 diabetic patients, classified as absent, mild, moderate, or severe neuropathy, by a fuzzy system based on clinical variables. Multichannel sEMG (64-electrode matrix) of tibialis anterior and gastrocnemius medialis muscles were acquired during isometric contractions at 10%, 20%, and 30% of the maximum voluntary contraction, and force levels during dorsi- and plantarflexion were recorded. Standard deviation and sample entropy of force signals were calculated and root mean square and sample entropy were calculated from sEMG signals. Differences among groups of force and sEMG variables were verified using a multivariate analysis of variance. Findings: Overall, during dorsiflexion contractions, moderate and severe subjects had higher force standard deviation and moderate subjects had lower force sample entropy. During plantarflexion, moderate subjects had higher force standard deviation and all diabetic subjects had lower entropy. Tibialis anterior presented higher root mean square in absent group and lower entropy in mild subjects. For gastrocnemius medialis, entropy was higher in severe and lower in moderate subjects. Interpretation: Diabetic neuropathy affects the complexity of the neuromuscular system during low-level isometric contractions, reducing the system's capacity to adapt to challenging mechanical demands. The observed patterns of neuromuscular complexity were not associated with disease severity, with the majority of alterations recorded in moderate subject. Highlights: Complexity was assessed with sample entropy as a measure of variability temporal construct. Higher amount of variability and lower force complexity were present in diabetics. Lower complexity of EMG of tibialis anterior was observed in diabetics. The majority of alterations in force complexity were observed in moderate cases. Neuromuscular complexity alterations were not associated with neuropathy severity.